Peningkatan Keterampilan Bercerita melalui Media Pembelajaran Exploding Box Siswa Kelas 2 SDN No. 146 Inpres Bontokanang Kabupaten Takalar - Mutmainna Mutmainna; Alien Bahri; Sri Rahayu (Journal on Education, 2023)
This type of research is classroom action research (classroom action research) which consists of two cycles where each cycle is held in two meetings. Research procedures include planning, implementation of action, observation and reflection. The subjects in this study were grade 2 students at SDN No. 146 Inpres Bontokanang Takalar Regency as many as 35 people. The research data is the teacher's assessment and student assessment in assessing storytelling skills in the learning process and learning outcomes. The data sources for this study were class teachers and 2nd grade students at SDN No. 146 Presidential Instruction of Bontokanang, Takalar Regency, totaling 35 people. The techniques used to collect data are: interviews, observation and documentation. Research process data were analyzed using qualitative descriptive techniques while learning outcome data were analyzed using quantitative descriptive techniques. The results showed that in the first cycle, out of 35 individuals, only 4 students or 11.42% met the minimum completeness criteria (KKM) or were in the very low category. Classically it has not been fulfilled because the average value is 89.62%. Whereas in cycle II where out of 35 students there were 31 people or 88.57% or were in the very high category they had fulfilled the KKM and classically had been fulfilled. Based on the results of the research above, it can be concluded that the learning outcomes of grade 2 students at SDN No. 146 Inpres Bontokanang Takalar Regency through exploding box learning media has increased.